2009
DOI: 10.1021/ma802243e
|View full text |Cite
|
Sign up to set email alerts
|

ROMP of Norbornene Monomers Carrying Nonprotected Amino Groups with Ruthenium Catalyst

Abstract: Amino acid-derived novel norbornene monomers (1a-2b) having nonprotected amino groups, together with tert-butoxycarbonyl (Boc) protected ones (1a-Boc-2b-Boc) were synthesized and polymerized by ring-opening metathesis polymerization using the Grubbs second generation ruthenium catalyst. The L-alaninederived endo,endo-monomer 1a with amino groups gave no polymer, while the exo,exo-isomer 1b gave a polymer by raising the catalyst concentration. N-Methyl-L-alanine-derived 2a and 2b carrying secondary amino groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 34 publications
3
49
1
Order By: Relevance
“…Interestingly however, amino acid-derived exo,exo-norbornene monomer 31 (Scheme 20) having unprotected methylamino groups undergoes ROMP to give the polymer in good yield. 66 The key for successful polymerization is the presence of appropriate spacers between the amino groups and the norbornene skeleton, and possibly intramolecular hydrogen bonding between the amino and carbonyl groups, which presumably prevents the amino groups from deactivating the catalyst. The methyl groups at the nitrogen atoms are also important, because analogous monomer 32 having primary amino groups shows Scheme 21 Possible regular structures of poly(endo,endo-2,3-disubstituted norbornene) (left) and poly(exo,exo-2,3-disubstituted norbornene) (right): R*, chiral group; H A and H B , two sets of nonequivalent olefinic protons distinguishable by 1 H nuclear magnetic resonance spectroscopy.…”
Section: Recent Advances In Rompmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly however, amino acid-derived exo,exo-norbornene monomer 31 (Scheme 20) having unprotected methylamino groups undergoes ROMP to give the polymer in good yield. 66 The key for successful polymerization is the presence of appropriate spacers between the amino groups and the norbornene skeleton, and possibly intramolecular hydrogen bonding between the amino and carbonyl groups, which presumably prevents the amino groups from deactivating the catalyst. The methyl groups at the nitrogen atoms are also important, because analogous monomer 32 having primary amino groups shows Scheme 21 Possible regular structures of poly(endo,endo-2,3-disubstituted norbornene) (left) and poly(exo,exo-2,3-disubstituted norbornene) (right): R*, chiral group; H A and H B , two sets of nonequivalent olefinic protons distinguishable by 1 H nuclear magnetic resonance spectroscopy.…”
Section: Recent Advances In Rompmentioning
confidence: 99%
“…Spectroscopic analysis by 1 H-1 H correlated spectroscopy nuclear magnetic resonance revealed that the polymer of 31 is syndiotactic-rich. 66 Molecular mechanics simulation suggested that this selectivity is kinetically caused by stability of metallacyclobutane intermediates rather than the thermodynamical stability of the product structures.…”
Section: Recent Advances In Rompmentioning
confidence: 99%
“…With monomer M1 in hand, ROMP with commercially available second-generation Grubbs catalyst was attempted. Using conditions modified from ROMP of amino acid-derived monomers, 21 we began by stirring a solution of M1 and 1 mol % Ru catalyst in THF at room temperature. The progress of the reaction was monitored by taking aliquots and evaluating by NMR spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was determined that 20 h was required to reach full conversion, and this prolonged reaction time (in comparison to ROMP with unfunctionalized monomers, see Supporting Information) was consistent with previous reports of ROMP with amine-containing monomers. 21 After quenching with ethyl vinyl ether and adding cold hexanes, a white solid was precipitated and isolated in quantitative yield (Table 1, entry 1). Analysis of the polymeric product by 1 H NMR spectroscopy shows characteristic broadening of signals typical of polymeric material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…34,35 For example, ring-opening metathesis polymerization (ROMP) was successfully employed to prepare a range of amino acid-functionalized homopolymers and block copolymers. [36][37][38] With regard to controlled radical polymerization formulations, atom transfer radical polymerization can be used to prepare similar copolymers. 39 However, reversible addition-fragmentation chain transfer (RAFT) polymerization seems to be preferred for such syntheses, presumably because of its superior tolerance of carboxylic acid functionality.…”
Section: Introductionmentioning
confidence: 99%